A survey of customizability in operating systems research. - Denys, G. (ACM computing surveys.)
An important goal of an operating system is to make computing and communication resources available in a fair and efficient way to the applications that will run on top of it. To achieve this result, the operating system implements a number of policies for allocating resources to, and sharing resources among applications, and it implements safety mechanisms to guard against misbehaving applications. However, for most of these allocation and sharing tasks, no single optimal policy exists. Different applications may prefer different operating system policies to achieve their goals in the best possible way. A customizable or adaptable operating system is an operating system that allows for flexible modification of important system policies. Over the past decade, a wide range of approaches for achieving customizability has been explored in the operating systems research community. In this survey, an overview of these approaches, structured around a taxonomy, is presented.